2020
DOI: 10.1051/e3sconf/202021601094
|View full text |Cite
|
Sign up to set email alerts
|

Definitions of useful energy and temperature at the outlet of solar collectors

Abstract: The article examines the solar collector of a solar water heating dryer using the example of drying ginger root (Zungiber). The diagram of a solar water heating drying unit is presented. The useful energy and temperature coming from the solar collector were analyzed using the model. The graphs are compared with the experimental results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…A study carried out on the drying of 3 types of mulberry silkworm cocoons revealed the optimum modes (temperature and time). It can be said that short time and medium temperature (combination) improve the final product and at the same time provide energy savings [15,16].…”
Section: Resultsmentioning
confidence: 99%
“…A study carried out on the drying of 3 types of mulberry silkworm cocoons revealed the optimum modes (temperature and time). It can be said that short time and medium temperature (combination) improve the final product and at the same time provide energy savings [15,16].…”
Section: Resultsmentioning
confidence: 99%
“…1. ), which belongs to the Asteraceae family of the Sunflower family and is 2 to 4 m high and weighs up to 300 g. Nowadays, it is believed that this vegetable is native to North America, where it grows in large quantities under natural conditions [2,6]. Ist development cycle is similar to that of potatoes [4,5].…”
Section: Introductionmentioning
confidence: 99%